Food Disgust Scale: Spanish Version - García-Gómez, Leonor; Romero-Rebollar, César; Hartmann, Christina; Siegrist, Michael; Ferreira, Guillaume; Gutierrez-Aguilar, Ruth; Villalpando, Salvador; Pacheco-Lopez, Gustavo (Frontiers in Psychology, 2020)
Introduction: The Food Disgust Scale (FDS) was recently developed and validated in Swiss adult population. This study aims to: 1) validate the FDS for the first time in a Spanish-speaking Mexican population, 2) correlate food disgust sensitivity with picky eating measures, and 3) explore the association between food disgust sensitivity and body mass index (BMI). Material and Methods: A Spanish version of the FDS (FDS-Sp) and its short version (FDS-Sp short) were tested with confirmatory factorial analysis (CFA) in order to test the original item/factor structure. Bivariate correlations were performed to determine the association between FDS-Sp / FDS-Sp short scores and picky eating. Lastly, hierarchical linear regression analysis was carried out to determine the relationship between food disgust sensitivity and BMI. Results: The factor structure of the FDS was replicated and acceptable internal consistency values were observed for FDS-Sp subscales (α varied between 0.781 and 0.955). Moreover, FDS-Sp subscales and FDS-Sp short were correlated with picky eating. Higher score in VEGI subscale of the FDS-Sp was a significant predictor for higher BMI, explaining 4% of the variance. Conclusions: FDS-Sp is a useful, reliable and robust psychometric instrument to measure the sensitivity to unpleasant food situations in a Mexican adult Spanish-speaking population. A relationship between food disgust sensitivity and picky eating, selective eating behaviors and neophobia in Mexicans was confirmed. BMI is multifactorial and only one subscale of FDS-Sp is a significant predictor for BMI status. These results are helpful to continue exploring food disgust in diverse populations.